Analisis Implementasi Pelayanan Dalam Penyelesaian Klaim pada Produk Mitra Mabrur Plus Asuransi Jiwa Syariah: Studi Kasus PT. AJS Bumiputera Cabang Medan - Nufikha, Liyundzira; Ramadhani, Sri; Syarvina, Wahyu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the application of services in resolving claims on products Mitra Mabrur Plus Syariah Bumiputera Life Insurance Medan Branch. This research is a qualitative descriptive study. The data collection technique used was interviews with Customer Managers, Agents and also several customers of Bumiputera Syariah Life Insurance Medan Branch. Observations and documentation were carried out at the Bumiputera Sharia Marketing Office, Medan Branch. The research results that have been obtained are the application of PT. Bumiputera Syariah Life Insurance Medan Branch in resolving Claims by providing Excellent Service at Bumiputera Syariah Life Insurance Medan Branch is in accordance with the concept including attiude (good attitude), attention (attention), action (fast action), ability ( having competent skills), appearance (diligent and neat appearance), Accountability (responsibility for all customers) and sympathy (providing a sense of sympathy for customers). Keywords: Syariah Life Insurance, Service Implementation, Claims